AB1167-HPR Cross-Cultural Adaptation, Reliability and Validity of the Turkish Version of the Upper Limb Functional Index (ULFI). (10th June 2014) - Tonga, E.; Gabel, P.; Tekindal, A.; Sarıal, C.
Abstract : Background: The Upper Limb Functional Index (ULFI) is a patient reported outcome measure with sound clinimetric properties and clinical viability for determination of upper limb status and impairment. To date, no validated Turkish version is available. Objectives: The purpose of this study is to cross-culturally adapted the ULFI for Turkish-speaking patients (ULFI-Tk) and determine the psychometric properties of reliability, validity, factor structure in a Turkish population with upper limb problems. Methods: The ULFI English version was culturally adapted and translated into Turkish and back-translated according to established guidelines. Patients (n=l02, 70% female, age 49.1±16.6) with upper limb disorders completed the ULFI-Tk at baseline and day-three for test-retest reliability. The Disability of Arm, Shoulder and Hand (DASH) Turkish version was concurrently completed as a criterion. Additional psychometric properties were determined for internal consistency (Chronbach's α), criterion validity and factor structure. Results: ULFI-Tk demonstrated good internal consistency (α=0, 87) and reliability (ICC=0.72, CI=0.58-0.80). Factor analysis demonstrated two factor structures, explaining 31, 23% of total variance. Pearson's correlation coefficient (r=0, 679;p<0, 05) revealed modarete criterion validity between the ULFI and DASH. Conclusions: The ULFI-TK demonstrated a 2 factor 25 item structure and is reliable and valid instrument. The ULFI-Tk consists of simple and easily understood words therefore it may be used to assess upper limb musculoskeletal disorders in Turkish speaking patients. References: Badalamente M, Coffelt L, Elfar J, Gaston G, Hammert W, Huang J, Lattanza L, Macdermid J, Merrell G, Netscher D, Panthaki Z, Rafijah G, Trczinski D, Graham B & American Society for Surgery of the Hand Clinical Trials and Outcomes Committee (2013b): Measurement scales in clinical research of the upper extremity, part 2: outcome measures in studies of the hand/wrist and shoulder/elbow. J Hand Surg Am 38, 407-412. Gabel CP, Michener LA, Melloh M & Burkett B (2010a): Modification of the Upper Limb Functional Index to a Three-point Response Improves Clinimetric Properties. J Hand Ther 23, 41-52 Gabel CP, Burkett B. The Upper Limb Functional Index: Development and Determination of Reliability, Validity, and Responsiveness. J Hand Ther. 2006;19:328–49. Gabel CP, Yelland M, Melloh M & Burkett B (2010b): A modified QuickDASH-9 provides a valid outcome instrument for upper limb function. BMC Musculoskelet Disord 10, 161. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4506